Lippincott's illustrated Q&A review of microbiology & immunology 2026-02-15T17:55:51+03:00 DEBUG: VuFind\ILS\Driver\Folio: Token taken from global cache: eyJhbGciOiJIUzI1NiJ9.eyJzdWIiO... - Buxton, B. A. (Bonnie A.) .); Gregg, Randal K.; Jensen, Lauritz A (Lippincott's illustrated reviews, 2010)

(untitled)
The book is heavily illustrated with photos of clinical manifestations or of gram-stained organisms, parasite eggs, oocysts or other parasitic stages, or pathologic specimens.Online access to the questions and answers provides flexible study options. And cover frequently tested topics in bacteriology, virology, mycology, parasitology, infectious disease, basic immunology, and clinical immunology